Rhamnolipids-based nanostructured lipid carriers: Effect of lipid phase on physicochemical properties and stability - Azevedo, Alexandra (2021)
In this work rhamnolipids were evaluated as surfactants for the production of nanostructured lipid carriers (NLCs). NLCs were produced by melt-emulsification using ultra-homogenisation followed by ultrasonication and different ratios of medium-chain-triglycerides and glycerol monostearate (lipid phase) were tested. NLCs presented sizes and polydispersity index values ranged between 97 and 120 nm and 0.200.26, respectively. Transmission electron microscopy observations confirmed the size and the spherical morphology of the NLCs. The thermal analysis and X-ray diffraction showed that the amount of solid lipid (glycerol monostearate) influences the melting, crystallisation and enthalpy of NLCs and their degree of crystallinity. Results showed that NLCs were more stable at 4 °C and the best formulation (1% of water phase, 0.05% of biosurfactant and solid:liquid ratio of 10:90) was stable for 30 days. This work showed the possibility of using rhamnolipids to produce NLCs and represent an important step for the development of lipid-based nanosystems using biosurfactants.